AI Integration in Real Estate Marketing : Implications from Vietnam - Trinh, Thi Van Anh; Mareš, Jan, 1986-; Špaček, Miroslav, 1954-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The objective of this qualitative study is to explore the integration of artificial intelligence (AI) in real estate marketing in Vietnam, examining its implications for stakeholders across the industry. The purpose of the study is to identify how AI tools and technologies are being adopted to enhance marketing strategies, improve operational efficiency, and address emerging consumer needs in the Vietnamese real estate sector. Through semi-structured interviews with real estate professionals, AI specialists, and marketing experts, this research aims to understand both the opportunities and challenges associated with AI adoption, such as cost, data infrastructure limitations, and workforce readiness. The central research question focuses on how AI is currently applied in Vietnam’s real estate marketing and the extent to which it influences decision-making, customer engagement, and market competitiveness. The study further investigates barriers to AI integration, including technological gaps, regulatory complexities, and cultural resistance to innovation. By analyzing these challenges, the research highlights potential strategies for overcoming adoption hurdles and maximizing AI’s transformative impact on the real estate industry. It is anticipated that the findings of this study will contribute valuable insights to both academic discourse and practical applications in Vietnam's real estate sector. By defining the role of AI in revolutionizing traditional marketing practices, this research underscores the importance of tailored government policies, industry collaboration, and targeted investments in technology. The ultimate goal of this study is to provide actionable recommendations that enable real estate developers, marketers, and policymakers to apply AI effectively, fostering sustainable growth and enhancing Vietnam’s competitive position in the global real estate market.
Vedoucí práce: Jan Mareš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses